Hygiene and legal aspects of occupational exposure assessment to cytostatics - Małgorzata Kupczewska-Dobecka; Anna Pałaszewska-Tkacz; Sławomir Czerczak; Katarzyna Konieczko (Nofer Institute of Occupational Medicine, 2018)
The employers responsibilities for the assessment of occupational exposure to cytostatics in the workplace were analyzed in the light of existing legal regulations. Cytostatics may pose a threat to health and life of workers taking care of patients treated oncologically, i.e., pharmacists, physicians, nurses and other personnel. The significant scale of occupational exposure to cytostatics in Poland is confirmed by the data collected in the Central Register of Data on Exposure to Carcinogenic or Mutagenic Substances, Mixtures, Agents or Technological Processes, maintained by the Nofer Institute of Occupational Medicine, Łódź, Poland. The issue of occupational risk assessment of exposure to cytostatics gives raise to numerous concerns. Polish regulations concerning health protection of employees occupationally exposed to cytostatics are not unequivocal, as they are derived from different areas of the law, especially those applying to hazard classification, labeling and preparation of safety data sheets for cytostatics. There are neither binding occupational exposure limits legally set for active compounds of antineoplastic drugs nor methods for monitoring of these substances concentrations in a worker's breathing zone and biological material. This prevents the employer to carry out the correct assessment of occupational exposure, the results of which are the basis for preparing the proper preventive strategy. In this article the consequences of amendments to the European chemical legislation for employers responsible for adequate protection of health and life of employees exposed to cytostatics, were discussed, as well as some legal changes aimed at a better health and life protection of workers exposed to cytostatics in a workplace were proposed. Med Pr 2018;69(1):77-92